The history of Superior, Wisconsin to 1900 - Wolner, Helen Marie (My University, 1939)
Chapters include: The Establishment of a City at the Head of Lake Superior, Life in Early Superior, Conditions at the Head of the Lakes During the Panic and the Civil War, A Period of Stagnation, A Renewal of Development at Superior, Superior: A Modern City.
1 v. (various pagings) ; 29 cm.